The application of uterine wall local resection and reconstruction to preserve the uterus for the management of morbidly adherent placenta: Case series - Xianlan Zhao; Ya Tao; Yingying Du; Lei Zhao; Cai Liu; Yan Zhou; Peng Wei (Elsevier, 2018)
Objective: We aimed to evaluate our experience with the application of uterine wall local resection and reconstruction to preserve the uterus in patients with morbidly adherent placenta. Materials and methods: In a retrospective study, data from patients with morbidly adherent placenta who delivered by cesarean section between January 1, 2013 and May 31, 2016 were analyzed. Prophylactic abdominal aorta balloon occlusion and tourniquet were used to prevent massive hemorrhage in all 62 cases, followed by uterine wall local resection and reconstruction to preserve the uterus. The quantity of estimated blood loss (EBL), operation time, and complications were analyzed. Results: The placenta penetrated to the myometrium in 10 cases, involved the posterior bladder wall in 46 cases, and penetrated the posterior bladder wall in six cases. For all cases, the mean EBL in the surgery was 1377.3 ± 605.2 mL, the mean EBL in the initial postoperative 24 h was 140.6 ± 66.3 mL, the mean operation time was 72.3 ± 24.5 min, and the mean postoperative hospital stay was 5.8 ± 1.6 days. The six cases of placenta penetrating the bladder underwent bladder repair. Sixty-one cases had preserved uterus, and only one case had a hysterectomy due to amniotic fluid embolism (AFE). Conclusion: Combined with prophylactic abdominal aorta balloon occlusion and tourniquet, uterine wall local resection and reconstruction is highly effective to reduce the intraoperative blood loss and hysterectomy in morbidly adherent placenta. Keywords: Abdominal aorta, Balloon occlusion, Cesarean delivery, Hysterectomy prevention, Morbidly adherent placenta